Management of Thyroglossal Duct Remnants: Our Experience - Arunkumar J. S.; Shibani Anchan; Santhosh S. G.; Muhammed Ahsan (Journal of Krishna Institute of Medical Sciences University, 2014)
Background: Thyroglossal duct remnants are more common in paediatric population. Complete excision of the tract is necessary to prevent recurrence. Sistrunk's surgery is done for thyroglossal duct remnants. This surgery has considerable failure rate. Aims and Objectives: This study was done to present our clinical experience regarding the successful management of thyroglossal cyst and fistula to know the role of imaging in prevention of recurrence after Sisktrunk's surgery. Material and Methods: This is an observational study of 15 cases of thyroglossal cyst and fistula. The data was collected retrospectively from the medical records of SDM College of Medical Sciences and Hospital. Results: No recurrence was seen in this series with a follow up period of 1 year. Conclusion: CT fistulography for thyroglossal fistula and USG neck for thyroglossal cyst is the imaging modality of choice. Nevertheless, it is pivotal to excise a wider core of tissue in revision cases to ensure complete cure to prevent possible recurrence.